The workload of flight attendants during short-haul flight operations: a system analysis - Bennett, Chloe Kayla (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Background and aim: Flight attendants forms a significant part in 24-hour aviation industry. Flight attendant fatigue is a significant problem in the aviation industry as it continues to jeopardize the ability to fulfil important safety and security roles which is critical in performance duty of a flight attendant. However, little attention has been accomplished to the workload, working conditions and fatigue of flight attendants crew in transport aircraft. In addition, there is currently less research that have also embraced the problematic of smaller regional/commercial operation (short-haul flight operations) inducing fatigue among short-haul flight attendants as the nature of this operation are often characterised with high productivity expectations in a demanding environment with high time pressures resulting in high workloads and fatigue. Thus, flight attendant fatigue and workload is a worldwide challenge in this operational environment and less attention has been given to the determining factors. Therefore, the aim of the study was to determine the workload factors contributing to flight attendant fatigue during short-haul flight operations. Methods (System analysis): To achieve the research aim, the work system analysis, based on the Smith and Carayon-Sainfort model was chosen as the main research approach which was conducted in two ways; based on existing literature and secondly based on expert interviews. This method provided a systemic aspect to understand the whole work system of flight attendants work during short-haul operations in order to identify all the contributing factors to flight attendant fatigue and workload. Results: The literature analysis and the data from the expert interviews highlighted significant findings to flight attendant fatigue and workload. The reasons for flight attendant fatigue operating short-haul flights can be found at organizational, task, individual, environmental levels and tools and technologies and due to the interaction of the factors. The main factors of flight attendants' fatigue are thought primarily as a function of scheduling due to irregular, mixed schedules with early starts and late finishes, extended duty days (long working hours), as well as high workload, due to the short turnaround flights, the number of sectors flown in a single duty period and duty length and high jobs demands. In addition, flight duty and rest regulations, confined work space in the cabin, vibrations, noise and lighting, sleeping in an unfamiliar environment, family responsibilities all add to additional stress placed on the body which can influence workload and sleep and consequently influencing fatigue. Conclusion: Overall the study determined that flight attendant fatigue is a significant problem in modern industry of short-haul operations. Using this systematic approach (work system analysis based on the framework of the work system model developed by Smith and Carayon-Sainfort (1989) allowed for an accurate representation of the complexity of flight attendant work environment in short-haul aviation industries, thus contributed to an increased understanding of fatigue and risk factors that span the entire work system and aid in identifying the patterns in combination of work system variables that are associated with increased risk to flight attendant fatigue. Overall flight attendant fatigue is a product of interactions with the short-haul environment. It can have a negative impact on safety, performance and well-being. Therefore, it needs to be managed and dealt with in the near future.
Keywords: Flight attendants -- Health and hygiene; Employees -- South Africa -- Workload